Achievement and Cost Efficiency Analysis of Implementing Green Construction on A Public Service Mall Construction in the City of - Rifqi Nur Mahmudi; Iskahar; Arif Kurniawan Suksmono (Jurnal Ilmiah Dinamika Rekayasa, 2024)
Green construction (GC) is a concept aiming at reducing the negative environmental impacts of construction activities during construction planning and implementation stages. The Public Service Mall Building Project in Tegal City is a building project that requires costs from planning to maintenance. The construction project certainly requires substantial costs. This research aims to evaluate the achievements and determine the cost efficiency of green construction. This research was conducted through a preliminary survey of the involved parties who understand the green construction concept to identify the most applied categories: the use of refrigerants without Ozone Depleting Potential (ODP), regional materials, environmental control over cigarette smoke, and pollution from construction activities. The type of research is qualitative, with data collection techniques carried out through interviews and direct observation. The data analysis for cost efficiency involves comparing green construction projects with non-green construction projects. The results of the benchmark measurements for using refrigerants without Ozone Depleting Potential (ODP), regional materials, and environmental control over cigarette smoke in the green construction projects achieved 100%, while the benchmark measurement results for green construction concerning pollution from construction activities achieved 50%. Based on the cost usage analysis of the upper structure construction of the Public Service Mall Building in Tegal City, the cost usage of the GC project is 9.25% more efficient than that of the conventional one.